Fulfillment of IFRS 2 disclosure requirements by companies listed on the Prague Stock Exchange - Martin Červený (European Financial and Accounting Journal, 2017)
The aim of this paper is to assess the quality of share-based payments' disclosure in compliance with IFRS 2 by companies listed on the Prague Stock Exchange. The study shows how companies in the Czech market utilizing share-based payments meet the requirements given by IFRS 2 framework and in order to support the arguments, it compares the results with randomly selected companies from the German DAX index, which represents a well-developed market. The focus is on three key principles of disclosure, as defined by the IFRS 2. As we will demonstrate, Czech corporations do meet the regulatory minimum requirements, but they fail to utilize some of the advanced valuation methods and their reports are generally rather brief compared to their German counterparts.
Keywords: M40; 650; Employee Stock Options; IFRS 2; Share-Based Payments